The Effectiveness of Charades Game in Teaching Vocabulary - Harmilawati Harmilawati; Ulfayanti; Sitti Aminah (Universitas Islam Ahmad Dahlan (UIAD), 2026)
This study aims to examine the effectiveness of using the Charades game in teaching English vocabulary to fifth-grade students at SD Negeri 141 Pakka. The participants of this study consisted of 15 students. This research employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The data were collected through observation, questionnaires, and tests, and analyzed using normality and homogeneity tests, a paired-sample t-test, and N-Gain analysis. The findings reveal that the implementation of the Charades game in the classroom was carried out very effectively, as indicated by the observation score of 96.43%. Students’ learning activities were categorized as very good (91.67%), and their responses toward the use of the Charades game were highly positive, with an average score of 89.7%. The results of the paired-sample t-test show a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. Furthermore, the N-Gain analysis reveals a score of 0.72 (72%), which falls into the high effectiveness category. These results indicate that the use of the Charades game has a significant and meaningful impact on students’ vocabulary mastery. Therefore, it can be concluded that the Charades game is an effective strategy for improving English vocabulary, while also enhancing students’ motivation and active participation in the learning process.